Evaluation of national health‐care related infection criteria for epidemiological surveillance in neonatology - Janita Ferreira; Maria C.F. Bouzada; Lenize A. de Jesus; Maria da Conceição Werneck Cortes; Guilherme A. Armond; Wanessa T. Clemente; Lêni M. Anchieta; Roberta M.C. Romanelli (Elsevier, 2014)
Objective: to assess the use of the Brazilian criteria for reporting of hospital‐acquired infections (HAIs) in the neonatal unit and compare them with the criteria proposed by the National Healthcare Safety Network (NHSN). Methods: this was a cross‐sectional study conducted from 2009 to 2011. It included neonates with HAI reporting by at least one of the criteria. Statistical analysis included calculation of incidence density of HAIs, distribution by weight, and by reporting criterion. Analysis of sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) for the national criteria was performed considering the NHSN as the gold standard, with agreement assessed by kappa. Results: a total of 882 newborns were followed, and 330 had at least one infection notified by at least one of the criteria. A total of 522 HAIs were reported, regardless of the criteria. An incidence density of 27.28 infections per 1,000 patient‐days was observed, and the main topographies were sepsis (58.3%), candidiasis (15.1%), and conjunctivitis (6.5%). A total of 489 (93.7%) were notified by both criteria, eight infections were notified only by the national criteria (six cases of necrotizing enterocolitis and two cases of conjunctivitis), and 25 cases of clinical sepsis were reported by NHSN criteria only. The sensitivity, specificity, PPV, and NPV were 95.1%, 98.6%, 98.4%, and 95.7%, respectively, for all topographies, and were 91.8%, 100%, 100%, and 96.3% for the analysis of sepsis. Kappa analysis showed an agreement of 96.9%. Conclusion: there was a high rate of agreement between the criteria. The use of the national criteria facilitates the reporting of sepsis in newborns, and can help to improve the specificity and PPV. Resumo: Objetivo: avaliar a aplicação dos critérios nacionais para notificação de infecções relacionadas à assistência à saúde (IRAS) em Unidade Neonatal e comparar com os critérios propostos pelo National Healthcare Safety Network (NHSN). Métodos: estudo transversal realizado de 2009 a 2011. Forma incluídos os neonatos que apresentaram notificação de IRAS por pelo menos um dos critérios. Análise estatística incluiu cálculo de densidade de incidência de IRAS e distribuição por peso e por critério de notificação. Foi realizada análise da sensibilidade, especificidade, valor preditivo positivo (VPP) e valor preditivo negativo (VPN) para os critérios nacionais, considerando o NHSN como padrão‐ouro e a concordância avaliada pelo Kappa. Resultados: foram acompanhados 882 neonatos, e 330 apresentaram pelo menos uma infecção notificada por, no mínimo, um dos critérios. Foram notificadas 522 IRAS, independentemente do critério. Observou‐se densidade de incidência de 27,28 infecções por 1.000 pacientes‐dia, e as principais topografias foram sepse (58,3%), monilíase (15,1%) e conjuntivite (6,5%). Um total de 489 (93,7%) notificações foram por ambos os critérios; oito infecções foram notificadas apenas pelo critério nacional (duas conjuntivites e seis enterocolites necrosantes); e 25 casos de sepse clínica foram notificadas apenas pelo NHSN. A sensibilidade, especificidade, VPP e VPN foram de 95,1%, 98,6%, 98,4%, 95,7%, respectivamente, para todas as topografias, e para análise de sepse foram 91,8%, 100%, 100% e 96,3%. O Kappa revelou concordância de 96,9%. Conclusão: verificou‐se uma elevada concordância entre os critérios. A utilização dos critérios nacionais facilita a notificação da sepse em neonatologia e podem contribuir para melhorar a especificidade e VPP. Keywords: Epidemiological surveillance, Infection, Neonatology, Newborn, Palavras‐chave: Vigilância epidemiológica, Infecção hospitalar, Neonatologia, Neonato